Wireless sensor networks and structural health monitoring: Experiences with slab track infrastructures. (March 2019) - Cañete, Eduardo; Chen, Jaime; Díaz, Manuel; Llopis, Luis; Rubio, Bartolomé
Slab track systems have the potential to become a more sustainable option for high-speed railway infrastructures than traditional ballasted tracks. Traditionally, the systems that monitor these infrastructures have been costly, but advances in the last few decades have made the use of wireless sensor networks within these infrastructures a feasible solution that can be used to evaluate their degradation for failure detection and prediction. Since the cost of these systems is steadily decreasing, it is now possible to use permanent wireless sensor networks as an integral part of the overall system to pave the way for smart infrastructures that can get real-time information about the structural health of the infrastructure at a relatively low cost. In order to show the suitability of this kind of system to monitor the structural health, three demonstrators, developed in the context of the FASTRACK project, related to the design and construction of a monitoring system for slab track systems that measures vibrations and displacements in the track, are presented. FASTRACK uses an innovative approach where data read by sensors are sent to passing trains, which are used as data mules to upload the information to a remote server. On arrival at the station, the data are stored in a database, which is queried by an application to extract relevant information by means of analysis algorithms to detect and predict failures. The first real scenario tests the limits of the system under stress situations. The second one tests the system in an actual, installed slab track to analyze the suitability of the communication architecture and to study a transition zone between slab tracks to a ballast track. The last scenario deals with the data mule performance tests.